(untitled) (BIRDEM Medical Journal, 2019)
Rickettsial fevers are a heterogeneous group of illness characterized by fever, headache, myalgia and rash. Rickettsia has a wide global distribution and regional species specificity. In spite of significant serosurveillance reports, rickettsial fevers are occasionally reported in Bangladesh. Here, we report a case of scrub typhus occurring in a young girl who presented with fever and had a typical eschar. We emphasize rickettsial fever should be a differential diagnosis in acute fever without localizing symptoms and signs in Bangladesh. Birdem Med J 2019; 9(1): 80-81